2015
DOI: 10.1097/pai.0000000000000124
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic and Predictive Significance of PARP-1 in Locally Advanced Breast Cancer of Egyptian Patients Receiving Neoadjuvant Chemotherapy

Abstract: PARP-1 immunohistochemical expression is a marker of good prognosis and is predictive of response to NCT in LABC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 44 publications
0
11
1
Order By: Relevance
“…After reviewing the complete text of the remaining 31 articles, 23 were excluded for the following reasons: review (10), no study endpoint (7), and insufficient data (6). Finally, a total of 3506 patients from eight eligible studies were included[ 7 9 , 15 19 ]. The details of the selection process are presented in Fig 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After reviewing the complete text of the remaining 31 articles, 23 were excluded for the following reasons: review (10), no study endpoint (7), and insufficient data (6). Finally, a total of 3506 patients from eight eligible studies were included[ 7 9 , 15 19 ]. The details of the selection process are presented in Fig 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, researchers reported that PARP inhibitors could be used to treat TNBC[ 6 ]; however, the relationship between the PARP expression level and TNBC is unclear. Recent studies have suggested that PARP over-expression is a poor prognostic marker for breast cancer survival[ 7 , 8 ]; nonetheless, contradictory evidence also has been reported[ 9 ]. These conflicting conclusions regarding the association between PARP expression and breast cancer clearly indicate the need for further investigation before application of this marker in future breast cancer diagnosis, treatment, and prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…However, Aiad et al (43) demonstrated that high nuclear PARP-1 expression levels were significantly associated with improved OS in locally advanced breast cancer; Klauschen et al (44) demonstrated that low nuclear expression levels of PARP were associated with a poor prognosis in pancreatic cancer. These previous studies indicated that PARP-1 expression had differing roles in between different tumor types and stages of the tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Donizy et al reported that nuclear-cytoplasm expression (NCE) of PARP-1 was associated with unfavorable prognosis in lymph node negative early breast cancer 21 . While in Aiad's study, the authors demonstrated that PARP-1 immunohistochemical expression is a marker of good prognosis in locally advanced breast cancer 22 . A meta-analysis included 3506 patients from eight studies, the results indicated that higher PARP expression indicated a worse clinical outcome in early stage breast cancer, with a HR of 3.08 (95% CI, 1.14 ± 8.29, P = 0.03) for disease-free survival and a HR of 1.82 (95% CI, 1.20 ± 2.76; P = 0.005) for overall survival 23 .…”
Section: Discussionmentioning
confidence: 97%
“…In their study, patients with high nPARP1 expression were more sensitive to anthracycline/taxane based neoadjuvant chemotherapy and with higher pathologic responses 14 . Results from Egyptian researchers also demonstrated that PARP1 immunohistochemical expression is predictive of response to anthracycline/taxane based neoadjuvant chemotherapy in locally advanced breast cancer patients 22 . As PARP1 involves in repairing DNA double-strand breaks, it is easy for us to understand its influence on sensitivity of agents which cause DNA damage, such as anthracyclines.…”
Section: Discussionmentioning
confidence: 97%